Balancing a seesaw – leaders perspectives on design and traditional quality improvement in healthcare. Issue 9 (18th April 2023) - Boström, Jonas; Hillborg, Helene; Lilja, Johan
Abstract : Purpose: The purpose of this paper is to explore and describe the perspectives and reasoning of senior development leaders in healthcare organizations, when reflecting on design as theory and practice in relation to more traditional methods and tools for improving quality and support innovation. Design/methodology/approach: The paper is based on a qualitative interview design with five development and innovation leaders from separate healthcare regions in Sweden. They have, to varying degrees, applied design theory and practice for quality improvement and innovation in their organizations. The interview transcript was analysed using a content analysis together with an interpretive approach. Findings: The major findings are to be found in the balancing act for leadership and organizations in healthcare when it comes to introducing and combining different theories and practices for improving quality and support innovation. The balance is between the change in power dynamics and pushing traditional boundaries in a complex healthcare world. Practical implications: The narratives from the leaders' experience of applying design theory and practice for improving healthcare quality can help us create readiness and knowledge about how we prevent and/or facilitate planning and implementing design theories, practices, methods and tools in a healthcare context. Originality/value: The study provides a unique insight when it captures and illustrates five different organizations' experiences when applying design for developing healthcare quality.